Implementasi E-Modul ARMOD dalam Pembelajaran Project-Based Learning untuk Meningkatkan Keterampilan Berpikir Analitik dan Literasi Digital Bioinformatika - Mahardika, Reza Dino; Isfaeni, Hanum; Rusdi, Rusdi (Universitas Negeri Jakarta, 2025)
The rapid development of data and technology in science encourages the collaboration of various disciplines to produce new branches of science, one of which is Bioinformatics, which studies molecular biology data stored in digital databases. The process of studying digital data requires special skills, such as analytical thinking skills and digital literacy. Efforts are needed to improve these two skills, one of which is by applying innovative teaching materials in project-based learning (PjBL). This study aims to determine the effect of the application of ARMOD E-Module teaching materials in PjBL on these two skills. Research with quasi-experimental methods and pretest-posttest control group design was conducted on students of the UNJ biology education study programme. The results showed that the application of ARMOD E-Module in PjBL can increase the average post-test in the aspects of segmentation ability, ability to connect system functions, ability to compare, ability to evaluate which are aspects of analytical thinking. The average post-test increases also occurred in the aspects of information and data literacy, communication and collaboration, digital content creation, security, and problem solving which are all aspects of digital literacy. The results of the one-way MANOVA test between the experimental class and the control class were 0.026, indicating a significant difference. The significant difference is thought to be due to the innovative features of teaching materials used in learning bioinformatics.